Prospects of Cross Border Energy Trade in South Asia - Gautam, Subas (Academia Research Journal, 2022)
The majority of South Asian nations use a combination of renewable energy sources like hydro, solar, and wind power together with nonrenewable energy sources like nuclear, coal, and natural gas to generate their electricity. Both of these sources are indigenous to some degree. Every nation in the area benefits from one type of resource or another. In India, coal is available. Natural gas is also abundant in Bangladesh, Pakistan, Nepal, and Bhutan, as well as hydropower. Using panel data from 2001 to 2015, this study examines the relationship between electricity consumption and changes in income, population, and foreign direct investment in Pakistan, India, Bangladesh, Sri Lanka, and Nepal, five South Asian nations. Additionally, the demand for electricity can be satisfied by imports or electrical production. The OLS results confirm that there is significant relationship between electricity consumption and GDP in South Asia. The OLS result further suggests that there is significant positive relation between GDP and electricity imports for India and Pakistan where as Nepal and Bangladesh have significant positive relation between GDP and electricity production. It is therefore concluded that there is a huge potential of cross border energy trade in South Asia and enhance economic growth in the region.